2018
DOI: 10.1186/s12939-018-0779-z
|View full text |Cite
|
Sign up to set email alerts
|

“We are everything to everyone”: a systematic review of factors influencing the accountability relationships of Aboriginal and Torres Strait Islander health workers (AHWs) in the Australian health system

Abstract: BackgroundHealth policy in Australia positions Aboriginal and Torres Strait Islander Health Workers (AHWs) as central to improving Aboriginal and Torres Strait Islander peoples’ health, with high expectations of their contribution to closing the gap between Indigenous and non-Indigenous health outcomes. Understanding how AHWs’ governance and accountability relationships influence their ability to address such health inequities has policy, programme and ethical significance. We sought to map the evidence of AHW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 47 publications
1
67
0
Order By: Relevance
“…Professional development opportunities for IHWs may have improved over the last few decades [35], however, this study identified ongoing issues such as IHWs not having opportunities to implement new learning in the workplace after the completion of training [8,35] and feeling underutilised in the workplace [8]. Strategies to address these issues include enhancing IHW roles, providing greater opportunities to apply skills in practice, improving IHW training, and ensuring that IHWs have opportunities to work to their full scope of practice [11,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional development opportunities for IHWs may have improved over the last few decades [35], however, this study identified ongoing issues such as IHWs not having opportunities to implement new learning in the workplace after the completion of training [8,35] and feeling underutilised in the workplace [8]. Strategies to address these issues include enhancing IHW roles, providing greater opportunities to apply skills in practice, improving IHW training, and ensuring that IHWs have opportunities to work to their full scope of practice [11,39].…”
Section: Discussionmentioning
confidence: 99%
“…In rural and remote healthcare in general, opportunity for career advancement is an important catalyst for retention [10]. The frustration experienced by IHWs in regard to lack of opportunities for career progression in both government and ACCHS sectors is well established [35], with such limited career pathways causing some IHWs to look for work outside the health sector [8]. This issue can be addressed through the development and implementation of succession plans and strong, clear career pathways [8,11,39].…”
Section: Discussionmentioning
confidence: 99%
“…43 In Australia, the Aboriginal and Torres Strait Islander Health Workers provide cultural mentorship to non-Aboriginal and Torres Strait Islander colleagues and advocate for culturally appropriate care. 28 Programmatic, social, management and political dynamics can shape the feasibility of cultural brokerage. For example, Brazilian CHWs felt their ability to elicit information about community needs was dependent on the long-term nature of their relationship with the neighbourhoods in which they work, 40 suggesting frequent staff turnover might constrain cultural brokerage.…”
Section: Findings Chw Function and Accountabilitymentioning
confidence: 99%
“…[22][23][24][25] Despite the fact that governmental CHW programmes generally entail the expectation that CHWs foster health system accountability to the community (and vice-versa), an accountability lens has not been widely applied to studies on CHWs, outside of several exceptions. [26][27][28][29] MeTHods This paper is a modified CIS. CIS is iterative and inductive, and it entails synthesising data across a diverse body of empirical literature and the development of new analytic propositions, synthesising arguments and questions.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…This may be because of the restricted availability of Indigenous interpreters and the shift in the role of AHWs from providing cultural support to activities requiring greater clinical skills and responsibilities . The limited availability of personnel to fulfil the linguistic and cultural needs of patients has reportedly resulted in burnout among the declining number of AHWs who act as both family or community members and clinicians . Cultural liaison officers and advisors can also facilitate cultural safety, but the lack of specific funding and supportive programs are barriers to establishing such positions.…”
Section: Discussionmentioning
confidence: 99%